Epidemiology of Fractures Sustained during Bike Accidents - Shaheryar Aziz Tarar, Aamir Waseem, Fraz Noor, Sikandar Ali Bhurgri, Naeem Mehmood Mughal, Abdul Samad Qureshi, (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To assess the epidemiological aspects of fractures sustained during bike accidents. Study design: Retrospective study Place and duration of study: Department of Orthopaedic, M Islam Medical & Dental College Gujranwala from 1st June 2020 to 31st December 2021. Methodology: Five hundred patients of bike accidents were assessed through severity scoring system. Various bike types, fractures sustained, rate of mortality, helmet usage was assessed. Results: There were 54.6% males and 45.4% females. The mean age of the patients was 33.5±5.75 years. Ninety percent of patients wear no helmet. The presentation of the injuries showed that majority of the cases as 28.2% had facial injuries. Spinal and thoracic injury was common in multi trauma injuries. Conclusion: Bike accidents cause severe life threatening injuries which can be reduced through wearing helmets.